HPTLC Quantification of Flavonoids, Larvicidal and Smoke Repellent Activities of Cassia occidentalis L. (Caesalpiniaceae) against Malarial Vectore Anopheles Stephensi Lis (Diptera: Culicidae) - Kadarkarai, Abirami Dhandapani* and Murugan (Journal of Phytology, 2011)
A simple High Performance Thin Layer Chromatographic (HPTLC) method has been developed for the analysis of flavonoid in ethanol extracts of Cassia Occidentalis. The amount of flavonoid in the extracts has been estimated by comparing the peak area using the standard. The proposed HPTLC method was found to be simple, faster and reliable for analysis of flavonoid. Cassia Occidentalis were the dominant invasive weed in the campus of Bharathiar University India. Their allelopathic activity has greatly affected the phytodiversity in the campus. With the view of their huge biomass prospecting, the larvicidal potential of ethanol extract of Cassia Occidentalis was tested against the larvae of Anopheles Stephensi. The ethanol extract of Cassia Occidentalis were found most effective with LC50 value of 60.69%, 64.76%, 67.78%, 70.56%, 92.21% of I, II, III, IV and pupa respectively. The smoke toxicity was more effective against the Anopheles stephensi. Smoke exposed gravid females oviposited fewer eggs when compared to those that were not exposed. Key words: HPTLC, Larvicid, Smoke Repellent, Cassia Occidentalis, Anopheles Stephensi Lis <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Abirami Dhandapani and Murugan Kadarkarai. HPTLC Quantification of Flavonoids, Larvicidal and Smoke Repellent Activities of Cassia occidentalis L. (Caesalpiniaceae) against Malarial Vectore Anopheles Stephensi Lis (Diptera: Culicidae). J Phytol 3/2 (2011) 60-71